1972
DOI: 10.1139/v72-548
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Conformation in the Ozonolysis of Acetals

Abstract: Six gauche conformations are theoretically possible for an acetal function and only three of them are reactive toward ozone. Each oxygen of the acetal function must have an electron pair orbital oreitned antiperiplanar to the C—H bond in order to be reactive toward ozone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…The fact that a very small movement of the iron atom out of the plane of the heme in hemoglobin [23] is coupled with much more major changes in protein structure should be a warning to bioorganic chemists wielding their curly arrows [24]. The stereo-electronic restrictions on reaction pathways as exemplified by Dunitz's view of the attack on a carbonyl group [25] or Deslongchamps' theory of how a tetrahedral intermediate collapses [26] will surely prove crucial to our understanding not only of the pathways of catalysis but also of the rates of the steps involved. It may be that, to discern such stereoelectronic restrictions, we shall need structural detail at very high resolution.…”
Section: Structurementioning
confidence: 99%
“…The fact that a very small movement of the iron atom out of the plane of the heme in hemoglobin [23] is coupled with much more major changes in protein structure should be a warning to bioorganic chemists wielding their curly arrows [24]. The stereo-electronic restrictions on reaction pathways as exemplified by Dunitz's view of the attack on a carbonyl group [25] or Deslongchamps' theory of how a tetrahedral intermediate collapses [26] will surely prove crucial to our understanding not only of the pathways of catalysis but also of the rates of the steps involved. It may be that, to discern such stereoelectronic restrictions, we shall need structural detail at very high resolution.…”
Section: Structurementioning
confidence: 99%
“…Previous studies had shown (2,3,9) that electron donors accelerate the reaction. However, one consequence of hkving a reaction series in a domain of temperature where reactivity is dominated by entropy factors, is to reverse the sign of p (1 3).…”
Section: Examination Ofmentioning
confidence: 98%
“…This relationship is called the isokinetic relationship (or the compensation effect) and may be written in the form of eq. [2] where p is the isokinetic temperature and 12, a constant. When such a relationship exists for a particular reaction series, P represents a point of inversion of reactivity., When P is higher than the experimental temperature range, then this represents a domain of temperatures where reactivity depends essentially on AH*.…”
Section: Examination Ofmentioning
confidence: 99%
See 2 more Smart Citations